Work family conflicts and the effect on the job satisfaction of female school principals in Eastern Province, Saudi Arabia - Abubakar, Jamila Muazu; Abdul Hamid, Jamaliah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The widely held premise that satisfied principals are likely to have better retention rates and serve as best advertisement for attracting future leaders has generated the need to consistently explore principals’ job satisfaction. With the recent leadership crisis of decreasing interest by teachers in taking up principalship positions and the issue of principals’ attrition, the need to explore and improve principals’ job satisfaction became ever more necessary. Using Frederick Herzberg’s Two Factor Theory of Motivator and Hygiene, this study assessed principals’ satisfaction with five facets of the job namely: the work itself, supervision, pay, promotion and coworkers. An additional purpose of the study was to determine which of these five facets of the job best predict principals’ overall job satisfaction. Using a sample of 160 female principals, the researcher found that principals were satisfied with the work itself, supervision and co-workers. They were dissatisfied with their pay and opportunities for promotion. Consistent with Herzberg’s Two Factor Theory of Motivator and Hygiene, the study found motivator factor “the work itself” as the strongest predictor of principals’ overall job satisfaction accounting for 41% of the variance. The results indicate that there were no significant differences in overall job satisfaction across age, years in principalship, school level and school size. Overall, principals were found to be satisfied with their job.